Systematic Literature Review: Etnomatematika dalam Kuliner Tradisional Indonesia - Riyan Setiawan; Rikayanti (Universitas Negeri Surabaya, 2026)
This study reviews various research works on ethnomathematics within Indonesian culinary traditions using a Systematic Literature Review (SLR) approach. The main goal is to identify dominant mathematical concepts, explore embedded cultural values, and highlight potential directions for future studies. Data were collected from Google Scholar following the PRISMA framework, resulting in 15 selected articles for analysis. Findings show that geometry is the most prominent concept, followed by measurement, arithmetic, and social arithmetic. Traditional foods such as lemang, onde-onde, and tumpeng illustrate three-dimensional geometric forms and the application of measurement and proportion in cooking processes. Cultural values like togetherness, precision, balance, and the preservation of tradition are reflected through these practices. However, most studies remain descriptive without empirical classroom application. Therefore, developing teaching materials and learning models based on culinary ethnomathematics is needed to promote more meaningful and contextual mathematics learning.